The Importance of Social Insurance in Human Capital Development (Eurasian Scientific Herald, 2023)
The article examines the essence of social insurance relations in the formation and development of human capital. Areas of employer enterprises that affect human capital have been studied. Specific features of social insurance types have been considered.